MENINGKATKAN KEMAMPUAN MENGHAFAL SURAH PENDEK MELALUI METODE ONE DAY ONE AYAT PADA KELOMPOK B DI TK SATU ATAP SDN 2 RIMO TAHUN 2023 - Widdia Sista Ariani Bancin; Mawaddah Nasution (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
one day one ayat method is a fun memorization method for children because it can be done with various models and techniques which can have a good effect on children's brain development. Due to the lack of facilities and techniques used, the learning process to improve children's memorization skills in the field is still less effective. One aspect of cognitive development or intelligence in children in the memorization process can be developed through this technique. Objective: This study aims to determine children's cognitive development in applying the One Day One ayat method to the ability to memorize short surahs. This type of research is qualitative research using a descriptive analysis approach. The subjects of this research were all children in Group B TK SDN 2 Rimo. Data collection techniques use observation, interviews and documentation. The data that has been collected is analyzed using descriptive analysis with data reduction techniques, data presentation and drawing conclusions. Data validity is carried out using triangulation techniques, namely technical triangulation and source triangulation. Results: that the application of the one day one ayat method cannot fully develop the short surah memorization abilities of group B children at One Roof Kindergarten SDN 2 Rimo. Because the obstacles to implementing the One Day One ayat method are that children rarely come, children are lazy about memorizing, and children are lazy about marojaah. So that the child's memorization does not increase and the time to complete it also increases than the target. Conclusion: The one day one ayat method is less effective in improving children's ability to memorize short surahs